Clemastine Fumarate Attenuates Myocardial Ischemia Reperfusion Injury Through Inhibition of Mast Cell Degranulation - Meng, Shuqi; Sun, Xiaotong; Juan, Zhaodong; Wang, Mingling; Wang, Ruoguo; Sun, Lina; Li, Yaozu; Xin, Anran; Li, Shuping; Li, Yao (Frontiers in Pharmacology, 2021)
Mast cell (MC) activation is associated with myocardial ischemia reperfusion injury (MIRI). Suppression of MC degranulation might be a target of anti-MIRI. This study aimed to determine whether clemastine fumarate (CLE) could attenuate MIRI by inhibiting MC degranulation. A rat ischemia and reperfusion (I/R) model was established by ligating the left anterior descending coronary artery for 30 min followed by reperfusion for 120 min. Compound 48/80 (C48/80) was used to promote MC degranulation. The protective effect of CLE by inhibiting MC degranulation on I/R injury was detected by cardiac function, 2,3,5-triphenyl tetrazolium chloride (TTC) staining, hematoxylin-eosin (HE) staining, arrhythmia, and myocardial enzyme detection. Inflammatory factor mRNA levels, such as TNF-α, interleukin (IL)-1β, and IL-6, were detected. Cultured RBL-2H3 mast cells were pretreated with CLE and subjected to C48/80 treatment to determine whether CLE suppressed MC degranulation. Degranulation of MCs was visualized using tryptase release, Cell Counting Kit-8 (CCK-8), and cell toluidine blue (TB) staining. RBL cells were conditionally cultured with H9C2 cells to explore whether CLE could reverse the apoptosis of cardiomyocytes induced by MC degranulation. Apoptosis of H9C2 cells was detected by CCK-8, the LDH Cytotoxicity Assay Kit (LDH), TUNEL staining, and protein expression of BAX and Bcl-2. We found that CLE pretreatment further inhibited cardiac injury manifested by decreased infarct size, histopathological changes, arrhythmias, MC degranulation, and myocardial enzyme levels, improving cardiac function compared with that in the I/R group. C48/80 combined with I/R exacerbated these changes. However, pretreatment with CLE for C48/80 combined with I/R significantly reversed these injuries. In addition, CLE pretreatment improved the vitality of RBL cells and reduced tryptase release in vitro. Similarly, the supernatant of RBL cells pretreated with CLE decreased the cytotoxicity, TUNEL-positive cell rate, and BAX expression of conditioned H9C2 cells and increased the cell vitality and expression of Bcl-2. These results suggested that pretreatment with CLE confers protection against I/R injury by inhibiting MC degranulation.